2019
DOI: 10.1016/j.conctc.2019.100378
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Signature Design- review of the biomarker guided adaptive phase –III controlled design

Abstract: Genomics having a profound impact on oncology drug development necessitates the use of genomic signatures for therapeutic strategy and emerging medicine proposals. Since its advent in the arena of clinical trials biomarker-related predictive methods for the identification and selection of patient subgroups, with optimal treatment response, are widely used. Genetic signatures which are accountable for the differential response to treatments are experimentally recognizable and analytically validated in phase II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…[26] The study by Bhattacharyya et al describes in detail the biomarker-guided adaptive phase III clinical trials, where first we need to identify significant genes among a large number of evaluated differential genes by high-throughput screening methods; second, estimate the gene-treatment interaction effect; and lastly, utilize an unknown-gene adaptive signature design to assess the level of significance in selecting differentially expressed genes by Bonferroni adjustment and false discovery rate. [27] BZW1, a member of the bZIP transcription factor superfamily, is involved in the progression of multiple tumors. Shi et al [28] found that highly expressed BZW1 can significantly promote the proliferation of prostate cancer cells by regulating the TGF-β1/Smad pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[26] The study by Bhattacharyya et al describes in detail the biomarker-guided adaptive phase III clinical trials, where first we need to identify significant genes among a large number of evaluated differential genes by high-throughput screening methods; second, estimate the gene-treatment interaction effect; and lastly, utilize an unknown-gene adaptive signature design to assess the level of significance in selecting differentially expressed genes by Bonferroni adjustment and false discovery rate. [27] BZW1, a member of the bZIP transcription factor superfamily, is involved in the progression of multiple tumors. Shi et al [28] found that highly expressed BZW1 can significantly promote the proliferation of prostate cancer cells by regulating the TGF-β1/Smad pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond being structured to allow formal analysis of sub-groups, there is also a large ethical benefit to these designs, exposing as few patients as possible to treatments from which they may not receive a benefit. Should no such pre-defined biomarkers be available, one might consider adaptive signature designs [168,169], also referred to as biomarker adaptive designs [149,170,171].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond being structured to allow formal analysis of sub-groups there is also a large ethical benefit to these designs; exposing as few patients as possible to treatments from which they may not receive a benefit. Should no such pre-defined biomarkers be available one might consider adaptive signature designs [168,169], also referred to as biomarker adaptive designs [150,170,171]. They aim to identify and use predictive biomarkers [170] during the trial.…”
Section: Discussionmentioning
confidence: 99%